CLUMSY VEIN, the Arabidopsis DEAH‐box Prp16 ortholog, is required for auxin‐mediated development. (16th December 2014) - Tsugeki, Ryuji; Tanaka‐Sato, Nana; Maruyama, Nozomi; Terada, Shiho; Kojima, Mikiko; Sakakibara, Hitoshi; Okada, Kiyotaka
Summary Pre‐messenger RNA (pre‐mRNA) splicing is essential in eukaryotic cells. In animals and yeasts, the DEAH‐box RNA‐dependent ATPase Prp16 mediates conformational change of the spliceosome, thereby facilitating pre‐mRNA splicing. In yeasts, Prp16 also plays an important role in splicing fidelity. Conversely, PRP16 orthologs in Chlamydomonas reinhardtii and nematode do not have an important role in general pre‐mRNA splicing, but are required for gene silencing and sex determination, respectively. Functions of PRP16 orthologs in higher plants have not been described until now. Here we show that the CLUMSY VEIN (CUV) gene encoding the unique Prp16 ortholog in Arabidopsis thaliana facilitates auxin‐mediated development including male‐gametophyte transmission, apical–basal patterning of embryonic and gynoecium development, stamen development, phyllotactic flower positioning, and vascular development. cuv‐1 mutation differentially affects splicing and expression of genes involved in auxin biosynthesis, polar auxin transport, auxin perception and auxin signaling. The cuv‐1 mutation does not have an equal influence on pre‐mRNA substrates. We propose that Arabidopsis PRP16/CUV differentially facilitates expression of genes, which include genes involved in auxin biosynthesis, transport, perception and signaling, thereby collectively influencing auxin‐mediated development.